Analisis Kecepatan, Kelincahan dan Daya Tahan Pemain Sepak Bola di Klub Sukodono FC - Khoirul Umam; Khoiril Anam (Multiverse: Open Multidisciplinary Journal, 2023)
This article aims to find out the speed, agility and endurance of the Sukodono FC football players. This research method uses quantitative methods with a survey design and descriptive methods. The instruments used in this study were the 30 meter Sprint test for speed, the Illinois Agility Run test for agility and the Multistage Fitness Test (MFT) test for endurance. The results of this study indicate that the physical condition of the soccer players for the Sukodono FC club is in the very poor and good category with a result of 43%. Meanwhile, based on the agility test obtained, it shows that the physical condition of the Sukodono FC club football players is in the good category with a result of 37%. Finally, based on the endurance test obtained, it shows that the physical condition of the Sukodono FC club football players is in the moderate category with a result of 45%.